2009
DOI: 10.1111/j.1754-9485.2009.02105.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an intensive nutritional program on daily set‐up variations and radiotherapy planning margins of head and neck cancer patients

Abstract: This is a prospective case-control study to assess nutritional supplementation in limiting weight loss and its impact on daily set-up variations and planning target volume (PTV) margins in head and neck (H&N) radiotherapy (RT). Twenty sequential H&N patients were recruited for this study. Ten patients had a percutaneous endoscopic gastrostomy (PEG) tube inserted prior to RT and 10 did not. PEG use was determined by departmental guidelines for patients considered at high risk for weight loss. Daily 2D electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…After excluding duplicate studies, and studies that did not meet the inclusion criteria based on reading title and abstract, 23 papers were selected for full-text examination. Eighteen papers were excluded; nine in which the target population was not clearly defined as patients with advanced cancer and/or treatment with curative intent was given [9,[14][15][16][17][18][19], four in which there was not given enough information to classify cachexia [20][21][22][23] and five in which the effect of other interventions than dietary counselling were evaluated [24][25][26][27][28]. The present review is thus based on two non-randomized studies and three RCT's.…”
Section: Search Results and Selection Of Studiesmentioning
confidence: 99%
“…After excluding duplicate studies, and studies that did not meet the inclusion criteria based on reading title and abstract, 23 papers were selected for full-text examination. Eighteen papers were excluded; nine in which the target population was not clearly defined as patients with advanced cancer and/or treatment with curative intent was given [9,[14][15][16][17][18][19], four in which there was not given enough information to classify cachexia [20][21][22][23] and five in which the effect of other interventions than dietary counselling were evaluated [24][25][26][27][28]. The present review is thus based on two non-randomized studies and three RCT's.…”
Section: Search Results and Selection Of Studiesmentioning
confidence: 99%
“…Four studies compared prophylactic vs. therapeutic PEG placement [58], four studies compared prophylactic PEG to oral/no PEG patients [9, 10], and two studies compared prophylactic PEG to therapeutic PEG and to oral patients (or pooled therapeutic and oral patients) [11, 12]. None of these studies reported swallow status from an instrumental swallow examination; instead, they reported weight loss, use of a feeding tube, or patient/clinician report as surrogate indicators of swallow function.…”
mentioning
confidence: 99%
“…Looking at weight loss as a possible measure of swallow function, the literature suggested that prophylactic PEG favors less weight loss over the course of RT treatment [5,9, 10, 1214]. Only one study, albeit a randomized clinical trial, found no significant difference in BMI change at the end of RT between patients who received prophylactic PEG vs. patients with therapeutic PEG or oral diets [11].…”
mentioning
confidence: 99%
“…The 20 head and neck cancer patients were included (3 patients were diagnosed with nasopharyngeal carcinoma). They found 4.9 and 11.0% of weight loss from baseline in PPEG group and non-PPEG group (Mercuri et al, 2009). But Silander et al (2011) conducted a randomised control trial to evaluate the effect of PPEG on malnutrition and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Nourishment can be undertaken via percutaneous endoscopic gastrostomy and inserting the feeding tube to the stomach through the abdominal wall before radiation, called "prophylactic percutaneous endoscopic gastrostomy" (PPEG). PPEG has been effective in the maintenance of weight, reduced set-up error, reduced hospitalisation, reduced treatment interruption and improved quality of life (Lee et al, 1998;Chang et al, 2009;Mercuri et al, 2009;Salas et al, 2009;Chen et al, 2010;Assenat et al, 2011;Silander et al, 2011).…”
Section: Comparison Of Treatment Compliance and Nutritional Outcomes mentioning
confidence: 99%